THE STUDY "REGISTER OF PATIENTS AFTER ACUTE STROKE (REGION)." Part 1. Hospital Prospective Register of Patients after Acute Stroke (According to the Results of the Pilot Phase of the Study) - S. A. Boytsov; S. Yu. Martsevich; N. P. Kutishenko; M. M. Loukianov; A. E. Mitichkin; R. V. Viskov; L. V. Stakhovskaya; N. A. Shamalov; G. P. Arutyunov; I. V. Kokareva; N. E. Parsadanyan; M. I. Chernyshova; et al. (Рациональная фармакотерапия в кардиологии)
Aim. To assess the main features of the clinical course of acute cerebrovascular accident (ACVA), its short-term and long-term outcomes and quality of pharmacotherapy based on hospital register. Material and methods. The hospital register of acute stroke (AS) was organized in one of the cardiovascular centers in Moscow city. The results of the pilot part of the study are presented (170 patients hospitalized from January 01, 2014 to September 30, 2014 with ACVA living in the service area of one of the closest outpatient clinics). Presence of cardiovascular diseases (CVD) and their risk factors (RF), prehospital therapy, short-term complications including death and pharmacotherapy recommended to survived patients were analyzed using hospital medical records. During ambulatory follow-up (prospective part of the register) the vital status and pharmacotherapy were assessed. Results. The majority of patients with AS had concomitant CVD (on average 2 per patient) and non CVD (on average 1.2 per patient). Data on the risk factors of CVD and their complications were reflected insufficiently in the medical records. Most patients in the prehospital period did not receive adequate treatment for the reduction in the cardiovascular risk. 90 patients survived and were discharged. 1.5-2 years after discharge, information on the vital status was available for 78 (86.7%) patients. 61 of them (78.2%) were alive and 17 (21.8%) died. Conclusion. The pilot part of the REGION register revealed that the majority of patients with AS have concomitant CVD and non-CVD. The overall quality of pharmacotherapy, primary and secondary prevention of ACVA was far from that recommended in clinical guidelines, especially during follow-up in outpatient clinic.